Satisfaction and psychological after effects of legal abortion at a tertiary care teaching hospital of North India. (18th August 2018) - Sharma, Richa; Radhakrishnan, Gita; Bhatia, M. S.; Gupta, Rashmi; Mehdiratta, Anita
Abstract: Psychological assessment using the Beck Depression Inventory II (BDI) on 196 eligible Medical Termination of Pregnancy (MTP) seekers showed that the depression rate prior to MTP was 12 (6.1%) and had increased to 21 (10.7%) 1 month after MTP. Risk factors included primipara, second-trimester abortion, MTP on humanitarian grounds (rape), foetal congenital anomalies and maternal illness. Psychological morbidity due to abortion greatly interferes with the interpersonal, spousal and mother–child relationships. This demands the need of counselling centres so that each MTP seeker could be counselled prior to and after MTP. Impact statement: What is already known on this subject? The association between abortion and depression has already been established. But there is a scarcity of information about the association between the psychological morbidity of abortion seekers, prior to and after legal abortions at a tertiary hospital. What do the results of this study add? Our study has not only evaluated the depression rate, but also evaluated the various individual psychological parameters of women with mild mood disorders which might go unnoticed and which certainly interferes with their interpersonal relationships. What are the implications of these findings for clinical practice and/or further research? Early diagnosis and interventions could help these women to have sound interpersonal relations.